2010
DOI: 10.1590/s0074-02762010000400011
|View full text |Cite
|
Sign up to set email alerts
|

Imaging techniques and histology in the evaluation of liver fibrosis in hepatosplenic schistosomiasis mansoni in Brazil: a comparative study

Abstract: Few publications have compared ultrasound (US) to histology in diagnosing schistosomiasis-induced liver fibrosis (LF); none has used magnetic resonance (MR). The aim of this study was to evaluate schistosomal LF using these three methods. Fourteen patients with hepatosplenic schistosomiasis admitted to hospital for surgical treatment of variceal bleeding were investigated. They were submitted to upper digestive endoscopy, US, MR and wedge liver biopsy. The World Health Organization protocol for US in schistoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…Our data suggest that the intensity of LF evaluated by imaging techniques or histology is not related, in a signifi cant number of patients, to portal hypertension, and severe portal hypertension has been reported in patients with minimal liver fi brosis 13,38 . The World Health Organization (WHO) grading of liver fi brosis by US should be reevaluated and used carefully in the defi nition of the severity of hepatosplenic schistosomiasis.…”
Section: Intensity Of Liver Fibrosismentioning
confidence: 62%
See 3 more Smart Citations
“…Our data suggest that the intensity of LF evaluated by imaging techniques or histology is not related, in a signifi cant number of patients, to portal hypertension, and severe portal hypertension has been reported in patients with minimal liver fi brosis 13,38 . The World Health Organization (WHO) grading of liver fi brosis by US should be reevaluated and used carefully in the defi nition of the severity of hepatosplenic schistosomiasis.…”
Section: Intensity Of Liver Fibrosismentioning
confidence: 62%
“…It uses strong magnetic fi elds and non-ionizing radiation in the radio frequency range, in contrast to CT scans and traditional X-rays, which both use ionizing radiation. Contrast agents may be injected intravenously to enhance the appearance of blood vessels, tumors or infl ammation [36][37][38][39][40][41][42][43] . …”
Section: Magnetic Resonance Imaging In Hepatosplenic Schistosomiasismentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that specifi c treatment for S. mansoni can contribute to decreasing infection levels and improving clinical conditions such as hepatosplenomegaly and PPF [15][16][17] . As a result, the regression of PPF may prevent the emergence of portal hypertension, highlighting the importance of PPF diagnosis by obtaining accurate methods for monitoring this disease 18 .…”
Section: Discussionmentioning
confidence: 99%